Guarding Tess [videorecording (DVD)] - MacLaine, Shirley, 1934-; Cage, Nicolas, 1965-; Wilson, Hugh, 1943-2018 (Columbia TriStar Home Video, 1998)
Shirley MacLaine and Nicholas Cage star in this comic compassionate look at life after the White House for two former Washington insiders: First Lady Tess Carlisle and Secret Service agent Doug Chesnic.